Tergitol-induced colonial growth without inhibition of conidiation - M. L. SPRINGER (Fungal Genetics Reports, 1991)
The cloning of genes from Neurospora crassa usually involves transformation of a mutant with genomic library DNA and the subsequent identification of transformants showing wild-type phenotype (Vollmer and Yanofsky 1986. Proc. Natl. Acad. Sci. 83:4869- 4873). This can be problematic in the case of morphological mutants, because the sorbose- containing medium that is typically used to promote colonial growth of the transformants tends to interfere with conidiation, and sometimes inhibits aerial hyphal growth altogether. The medium described below uses the nonionic detergent tergitol (Tatum et al. 1949. Science 109:509-511) to induce colonial vegetative growth without affecting aerial hyphal growth or morphology.